2014
DOI: 10.1002/anie.201406858
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Surface‐Drying Properties of Bioadhesive Proteins

Abstract: Sessile marine mussels must “dry” underwater surfaces before adhering to them. Synthetic adhesives have yet to overcome this fundamental challenge. Previous studies of bio-inspired adhesion have largely been performed under applied compressive forces but these are poor predictors of an adhesive’s ability to spontaneously penetrate surface hydration layers. In a force-free approach to measuring molecular-level interaction via the surface water diffusivity, different mussel foot proteins were found to have diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 23 publications
2
58
0
Order By: Relevance
“…[26] In addition, it was recently reported that positively charged primary amine groups in mussel adhesive proteins can breach the hydrated salt layer in saline water and assist the catechol in forming as trong bidentate adhesion to inorganic surfaces in wet conditions. [21,32] This synergistic collaboration of catechol and amine groups supports the observed stronger adhesion of ap NE coating compared to that of pPC.F urthermore,D HBA, the intermediate of NE polymerization, exhibited less and also slower auto-oxidation than catechol compounds without an electron-withdrawing group,such as PC. [21] In summary,this work demonstrates for the first time that the introduction of an amine functional group to the poly-(catechol) coating significantly enhances (almost 30-times higher) the adhesion and deposition capability of catecholbased polyphenolic coatings.T he origin of the strong attraction between the poly(catecholamine) layers is most likely due to various physical interactions,such as surface salt displacement by the primary amine, p-p stacking (the quadrupole-quadrupole interaction of indolic crosslinks), and cation-p interaction (the monopole-quadrupole interaction between positively charged amine groups and the indolic crosslinks).…”
Section: Methodssupporting
confidence: 52%
“…[26] In addition, it was recently reported that positively charged primary amine groups in mussel adhesive proteins can breach the hydrated salt layer in saline water and assist the catechol in forming as trong bidentate adhesion to inorganic surfaces in wet conditions. [21,32] This synergistic collaboration of catechol and amine groups supports the observed stronger adhesion of ap NE coating compared to that of pPC.F urthermore,D HBA, the intermediate of NE polymerization, exhibited less and also slower auto-oxidation than catechol compounds without an electron-withdrawing group,such as PC. [21] In summary,this work demonstrates for the first time that the introduction of an amine functional group to the poly-(catechol) coating significantly enhances (almost 30-times higher) the adhesion and deposition capability of catecholbased polyphenolic coatings.T he origin of the strong attraction between the poly(catecholamine) layers is most likely due to various physical interactions,such as surface salt displacement by the primary amine, p-p stacking (the quadrupole-quadrupole interaction of indolic crosslinks), and cation-p interaction (the monopole-quadrupole interaction between positively charged amine groups and the indolic crosslinks).…”
Section: Methodssupporting
confidence: 52%
“…Hence, mfp3S-pep-3Dopa is able to displace interfacial water molecules from the TiO 2 substrate surface and additionally interacts with surface OH groups via a ligand exchange reaction. In contrast to other techniques characterizing surface hydration, e.g., overhauser dynamic nuclear polarization (ODNP), [32] which requires extensive surface preparation/modification, ATR-FTIR provides a noninvasive in situ real-time determination of both liquid-like and surface bond water. [33] …”
Section: Resultsmentioning
confidence: 99%
“…Compared to hydrophilic surfaces, hydration layers are easier to remove from hydrophobic surfaces because the layer is less strongly attached to this type of surface. Akdogan et al studied the diffusion dynamics of surface water, either on hydrophobic polystyrene (PS) or hydrophilic silica (SiO 2 ) surfaces, in the presence of various mfps, i.e., mfp‐1, mfp‐3s, and mfp‐5 . By measuring the diffusion coefficient of the surface‐bound water molecules, the ability of mfps to perturb the surface water dynamics was used as an indication of the intimacy between surfaces (PS or SiO 2 ) and mfps.…”
Section: Catechol‐based Materials Used As Underwater Adhesivementioning
confidence: 99%
“…Catechols have a versatile character; they are able to interact to substrates via hydrogen bonding, metal–catechol coordination or cation–π complexation . Moreover, both natural and synthetic polymer chains (containing amphiphilic or ionic features) can be self‐adjustable . That means that depending on the target surface, different parts of the adhesive are exposed to the surface ensuring strong adhesive bonding.…”
Section: Perspectivesmentioning
confidence: 99%